Portfolio elektronik sebagai asesmen pembelajaran fisika - Sabana Asmi; Wiyanto Wiyanto; Ian Yulianti (Universitas Sultan Ageng Tirtayasa, 2021)
One of the technologies available to support the assessment process is the e-portfolio. Much research has been done for e-portfolio assessment, and the result can easily find the result in journals. Even though systematic study about e-portfolio as physics learning assessment still rarely done. This research aims to identify the role of e-portfolio as a physics learning assessment in school. A literature study is carried out using four procedures based on PRISMA that are (1) identification, (2) screening, (3) eligibility, and (4) included. Article search has been done through the DOAJ, ERIC, IOP Science, Science Direct, and Springer Link. Based on analysis results, the use of e-portfolio encourages the creation of self-regulation learning. Furthermore, self-regulation learning can help develop a metacognitive skill that students much need for learning physics. Even so, based on 220 articles identified, research about e-portfolio as physics learning assessment has not been found. Therefore, further research is needed to develop and implement an e-portfolio as a physics learning assessment.